Ab initio identification of the Li-rich phase in LiFePO4. Issue 25 (18th June 2018) - Zeng, Hua; Gu, Yue; Teng, Gaofeng; Liu, Yimeng; Zheng, Jiaxin; Pan, Feng
Abstract : This article provides a systematic theoretical study of Li-rich phase Li1+x Fe1− x PO4 ( x ≤ 12.5%) cathode materials for lithium-ion batteries. Abstract : A recent discovery of anionic redox activity in Li-rich layered compounds opens a new direction for the design of high-capacity cathode materials for lithium-ion batteries. Here using extensive ab initio calculations, the thermodynamic existence of the Li-rich phase in LiFePO4 to form Li1+ x Fe1- x PO4 with x not exceeding 12.5% has been proved. Anionic redox activity and structural stability during delithiation are further investigated. Interestingly, it is found that Li1+ x Fe1− x PO4 cannot be delithiated completely and thus cannot achieve extra capacity by anionic redox activity, because the local oxygen-ion redox will cause the fracture of the rigid framework formed by phosphate tetrahedral polyanions. Although an extra capacity cannot be realized, the excess Li-ions at Fe sites can enhance the Li-ion diffusivity along the adjacent [010] channel and contribute to the shift from 1D to 2D/3D diffusion. This study provides a fresh perspective on olivine-type LiFePO4 and offers some important clues on designing Li-rich cathode materials with high energy density.